THE INFLUENCES OF ELECTRONIC-BASED GOVERNMENT SYSTEM (SPBE) IMPLEMENTATION ON PERFORMANCE ACCOUNTABILITY IN THE REGIONAL SECRETARIAT OF SOUTH SULAWESI PROVINCE - Almadani, Muzzaman; Cahyani, Andi Asniar Dewi; Khadafi, Muhammad (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
This research investigates the impact of implementing the Electronic-Based Government System (SPBE) on performance accountability within the Regional Secretariat of South Sulawesi Province. The research addresses a discrepancy where performance assessments based on accountability reports from the Regional Secretariat do not align significantly with the SPBE assessment index. Adopting a quantitative, descriptive methodology, the research surveyed civil servants working across various units of the Regional Secretariat in South Sulawesi Province. Data was collected using a questionnaire validated for reliability through Statistical Package for the Social Sciences (SPSS). The findings indicate a significant positive influence of SPBE implementation on performance accountability within the Regional Secretariat of South Sulawesi Province.